Mouse models of myeloproliferative neoplasms for pre-clinical testing of novel therapeutic agents - Stetka, Jan; Skoda, Radek C. (Biomedical papers, 2021)
Myeloproliferative neoplasms (MPN), are clonal hematopoietic stem cell (HSC) disorders driven by gain-of-function mutations in JAK2 (JAK2-V617F), CALR or MPL genes. MPN treatment options currently mainly consist of cytoreductive therapy with hydroxyurea and JAK2 inhibitors such as ruxolitinib and fedratinib. Pegylated interferon-alpha can induce complete molecular remission (CMR) in some MPN patients when applied at early stages of disease. The ultimate goal of modern MPN treatment is to develop novel therapies that specifically target mutant HSCs in MPN and consistently induce CMR. Basic research has identified a growing number of candidate drugs with promising effects in vitro. A first step on the way to developing these compounds into drugs approved for treatment of MPN patients often consists of examining the effects in vivo using pre-clinical mouse models of MPN. Here we review the current state of MPN mouse models and the experimental setup for their optimal use in drug testing. In addition to novel compounds, combinatorial therapeutic approaches are often considered for the treatment of MPN. Optimized and validated mouse models can provide an efficient way to rapidly assess and select the most promising combinations and thereby contribute to accelerating the development of novel therapies of MPN.
Keywords: MPN; myeloproliferative neoplasms; JAK2; mouse model; pre-clinical models; novel therapies